Simulation Studies on Vertical Offset Non-Circular Journal Bearing Profile - Saroj Bala (Japanese Society of Tribologists, 2014)
In the present simulation study, the performance characteristics of vertical offset non-circular journal bearing have been evaluated. During study, the thermal pressures have been found of increasing nature with increase in speed in both the lobes of the bearing. A considerable rise in oil-film temperature and thermal pressure has been found in lower lobe and comparatively a low rise in oil-film temperature and thermal pressures has been found in upper lobe of the bearing. The trend for variation of oil-film temperature with speed has been found of increasing nature. The load capacity, power loss in the bearing and bearing characteristics Sommerfeld number has been observed to be of increasing nature with speed. It has been concluded that more than one lobe have been reported in the bearing profile under study, thus the profile can be considered as an alternate to circular journal bearing for better stability applications.